PERCEPTUAL ANSWERS PRESENTED BY SOCCER ATHLETES DURING PRE AND POST-TRAINING PERIODS: A SYSTEMATIC REVIEW WITH METANALYSIS (Fiep Bulletin - online, 2020)
Perceptual training plays an important role during the teaching and learning process of athletes. This process should be aimed at the development of perceptions, thus improving motor skills and physical abilities of athletes, seeking new methodologies and techniques to make this process easier. Visual perception has a very important cognitive function during the training periods, because when new technologies are introduced for the development of visual perception, they can provide an interesting learning, as well as contribute to the reduction of reaction time, accuracy of athletes. The objective of the present study was to analyze the perceptual responses in athletes during the pre- and post-training periods. This is a systematic review with meta-analysis of randomized clinical studies that analyze the perceptual trainings in athletes, without language restrictions and with dates of studies with at least 20 years, in the following databases: Pubmed, ScienceDirect, ClinicalTrials, VHL (LILACS and MEDLINE), SCOPUS, EBSCO, SciELO, as well as the gray literature base: OpenGrey.eu, DissOnline, and the Reasearch Gate. Three articles were analyzed and comparisons were established between the pre- and post-training periods. After all triage, three articles were analyzed in full and established comparisons between pre-workout, post-workout and control groups. The main results were: Comparison between the training of the post-experimental and post-control groups, with 95% CI between 0.51 and 2.32%. The overall effect test yielded p = 0.02, revealing that such difference was significant. However, the heterogeneity, I² = 62% p value = 0.07, was high. Comparison between pre-experimental and post-experimental training, with 95% CI between -1.60 and 19.40%. The test for the general effect obtained p